Menciptakan Lingkungan Sekolah Harmonis dengan Sosialisasi Stopp Bullying di SDN 01 Pojok Kecamatan Ngantru Kabupaten Tulungagung - Nida Nur Khansa; Misbakhul Khaer; Nur Wahyuni (STAI Senori Tuban, 2026)
The low level of students’ understanding of the forms and impacts of bullying, along with the insufficient involvement of teachers and parents in prevention efforts, has become a major barrier to creating a safe, comfortable, and harmonious school environment. This Community Service Program (PKM) aims to enhance awareness and collective responsibility among all school stakeholders in preventing bullying through structured stop-bullying socialization activities. The program employed an educative–participatory community service approach, implemented through several stages, including field observation, problem identification, program planning, the implementation of socialization activities using counseling, interactive discussions, and role-playing methods, and concluded with an evaluation and follow-up phase in the form of a collective anti-bullying commitment. The results of the program indicate an increase in students’ understanding and awareness of the dangers of bullying, a strengthening of teachers’ roles in supervising and guiding student behavior, and increased parental involvement in children’s character education. Furthermore, the program successfully fostered a shared commitment among all members of the school community to creating a child-friendly and harmonious learning environment